Peranan Restrukturisasi Utang dalam Melindungi Perseroan Terbatas dari Kepailitan Berdasarkan Undang-Undang Nomor 37 Tahun 2004 - Karyn, Khanza Octalivia; Lewiandy (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research analyzes a fundamental academic problem in Indonesia's bankruptcy law lies in the tension between the spirit of business rescue through Suspension of Debt Payment Obligations (PKPU) and the rigidity of the